Borneo batik pattern production concept - Salbiah Kindoyop; Mohammad Puad Bebit; Mfazmi Hisham (Penerbit Universiti Malaysia Sabah, 2024)
Batik art is famous with unique designs and patterns, which display the beauty of textile art and reflect the values and cultural identity of the community. In Malaysia, there are four main motifs recognized: floral, fauna, geometric, and abstract patterns. Among the popular motifs are plants such as bamboo shoots, ylang-ylang flowers, champaca, and others. The batik art in Sabah also possesses its own unique characteristics and identity based on its designs and patterns. This paper discusses the concept of producing contemporary batik patterns in Sabah, focusing on aspects of creativity and beauty. Additionally, this study analyzes the techniques used in producing Sabah batik patterns, which serve as symbols of cultural identity and pride for the local community. The research employs a qualitative approach, with data collected through interviews with batik makers and cultural experts to analyze the creativity of Sabah batik. Furthermore, this study reveals the beauty in the creation of Sabah batik patterns that combine traditional elements with innovative motifs inspired by nature. In conclusion, Sabah batik is a beautiful artistic manifestation, representing an important iconic symbol of Sabah's cultural identity. This paper contributes to a deeper understanding of traditional arts such as Sabah batik, ensuring its continued relevance and influence in the modern world through the production of contemporary batik patterns in Sabah.